Partial Internal Control Recovery on 1-D Klein-Gordon Systems - Iwan Pranoto (Institute for Research and Community Services (LPPM) ITB, 2010)
In this exposition, a technique to recover internal control on a distributed parameter system is reported. The system is described by 1-D Klein- Gordon partial differential equation with a time-varying parameter. We would like to recover the internal control applied to the system if we know some limited information about the output. We use a method called sentinel method to recover the internal control. It involves some construction of a linear functional, and we show that this construction relates closely to the exact controllability problem.